Magnetic field effects in ferrocenealkane thiol self assembled monolayer modified electrodes - LYONS, MICHAEL (My University, 2010)
The redox behaviour of well characterized ferrocene alkane thiol self assembled monolayer modified electrodes in contact with aqueous perchlorate solutions both in the absence of and in the presence of an external magnetic field is examined using both electrochemical and gravimetric techniques The redox switching process has been shown to involve an ET reaction involving the ferrocene/ferricinium redox transition coupled with an ion pairing step involving perchlorate ion. It has been shown that the voltammetric response recorded in the latter medium is irreversibly effected by the imposition of a static magnetic field of magnitude 0.5 T applied in a direction parallel to the electrode surface. Both the surface coverage of electroactive ferrocene surface groups and the electrochemical rate constant for the ferrocene/ferricinium surface redox transformation is quantitatively influenced by the imposition of the external magnetic field. It is suggested that the latter redox transformation is accompanied by ion pair formation between the ferricinium and perchlorate ions . The magnetic field dependence of the redox behaviour can be attributed to structural changes in the monolayer arising from double layer effects involving changes in the spatial distribution of perchlorate counterions at the monolayer/solution interface, the latter brought about by local convective stirring arising from the B field generated magnetohydrodynamic Lorenz body force.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; Self Assembled Monolayer; Magnetoelectrochemistry; Nanoscience & Materials; Smart & Sustainable Planet